Walking bureaucracy: the case of companions in the youth policies of Santa Fe`s province (Papeles, 2023)
In this article we present some advances in the Research Projects that we have been developing since 2021, based in the School of Social Work of the Faculty of Political Sciences and International Relations of the National University of Rosario (PID UNR). We recover here one of the findings of the Project in which we problematize the self- and heteroperception of companions as state bureaucracy even when in most cases they are not agents hired directly by the state. We are specifically interested in working on how they construct the sense of considering themselves the state in their interaction with children and young people. For this purpose, we organize the document as follows. Firstly, we present the objectives and methodological approach of the previously referenced PIDs. In a second moment, we describe the institutionality of the Ministry of Social Development of the Province of Santa Fe and then point out the outstanding characteristics of the Labor Insertion Programs for young people from popular sectors dependent on that state agency, focusing on what constitutes our unit. of analysis: the Santa Fe Más. Finally, we problematize the idea of ​​companions as street bureaucracy, pointing out the tensions around said name
Keywords: bureaucracies; accompaniments; youth; social development